Statistical modelling of ozone concentration in troposphere - Girgždienė, Rasa; Rekašius, Tomas (Lietuvos matematikos rinkinys, 2002)
Statistical analysis of the ozone concentration data received from the background monitoring stations located in Lithuania is performed. The goal of the study is modelling of ozone background concentration trend-cycle component. The regression models obtained include ozone concentrations at foregoing moments, local meteorological factors (such as air temperature, solar activity, wind speed and its direction, ect.), their lags and interactions.